Analisis Penentuan Distribusi Center Alat Bantu Dengar di PT. Nobel Jaya Mandiri Menggunakan Metode Pusat Gravitasi (Center of Gravity) - Alqorni, Wais; Murnawan, Hery (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Nobel Jaya Mandiri is a company engaged in hearing labs and sales of assistive devices under the brand name Nobel Audiology which has 32 branches throughout Indonesia, one of which is located in Surabaya. Currently, the company plans to open another new branch in the Surabaya area to provide optimal service. In 2023, there will be 793 new customers domiciled in Surabaya, meaning that 0.03% of Surabaya people experience hearing problems. Therefore PT. Nobel Jaya Mandiri will improve location services by calculating using the center of gravity method, ranking procedure, investment analysis, and risk management. The candidate for the new branch is RS. Mayapada Surabaya(18.793.8 Km ,Rp.131.178.600) investment cost Rp. 52.473.000 with high risk. Mitra Keluarga Satelit Surabaya Hospital (21,602.7 km, Rp.151,218,900) investment cost Rp.28,473,000 with high risk and Ruka in VBM area (18,735.6 km, Rp.131,149.200) investment cost Rp. 137,473,000 with low risk. so the company chose Ruko Villa Bukit Mas because of the consideration of good center of gravity results with a large enough investment but minimal risk. Keywords: Investment, Location, Methode gravity, Risk